FMO1 gene expression independently predicts favorable recurrence-free survival of classical papillary thyroid cancer. (13th February 2018) - Luo, Jing; Zhang, Bowei; Cui, Likun; Liu, Tong; Gu, Yi
Aim: To examine the expression profile of FMO1 in papillary thyroid cancer (PTC) and its prognostic value in recurrence-free survival (RFS).Methods: A retrospective analysis was performed using data from the Cancer Genome Atlas and Human Protein Atlas.Results: The most frequent variants of PTC had decreased FMO1 expression compared with their respective adjacent normal tissues. However, even under the best cut-off model, high FMO1 expression was only significantly associated with better RFS in classical PTC (p < 0.001), but not in other two variants. High FMO1 expression independently predicted favorable RFS (hazard ratio: 0.202; 95% CI: 0.084–0.487; p < 0.001) in classical PTC.Conclusion : High FMO1 expression might serve as a biomarker that independently predicts favorable RFS in classical PTC patients.